PROSES PENERAPAN KONSEP RESTORATIVE JUSTICE DALAM KASUS TINDAK PIDANA PEMBUNUHAN - Bimo Putro Raharjo (2018)
Implementation of Restorative Justice to resolve cases in Murder, Restoration of Justice is a system of settlement of crime committed by a perpetrator solving his problem outside the litigation system. As regulated in the concept of restorative justice that emphasizes to the perpetrators and victims. However, Substantive criminal law and criminal procedure differ greatly from the principle of restorative justice, there are criminal cases that differ from the sentence. So the concept of restorative justice should be based on the interests of victims and perpetrators based on an agreement, overriding the formal criminal law in Indonesia, this should be noted for the creation of a just law for all the people of Indonesia. Many cases end up in prison resulting in overcapacity. Once the method of this paper is juridical-normative to know about the application of developing law.